REVIEW OF BODY SNATCHING TO BODY DONATION: PAST AND PRESENT: A COMPREHENSIVE UPDATE - MAITREYEE MUTALIK, (International Journal of Pharma and Bio Sciences, 2015)
Dissection of a human body by medical students has been an indispensible part of medical education and medical research in general, and hence human cadavers have always remained one of the most important teaching tools. History reveals that it was a great challenge for early anatomists to obtain human bodies for dissection purpose. With increasing demand of human cadavers and illegal practices to obtain them, the law had to play its role, and the ‘Anatomy Acts’ were formed in various countries. These acts not only empowered medical teaching institutions to obtain unclaimed bodies, but also opened a gateway for willful body donation. ‘Body donation’ is a willful act of offering one’s body after death for medical research and education. The concept of body donation has been gradually penetrating in society. The quest of human mind for knowledge has seen an interesting journey from body snatching to body donation.